Penggunaan Video Pembelajaran dalam Peningkatan Keterampilan Berpikir Kritis Siswa - Nisa, Lutfiatun; Maulida, Nazwa; Latifah, Cindy; Renaldi, Rizal (Indo-MathEdu Intellectuals Journal, 2026)
The use of instructional videos has become an increasingly popular strategy in elementary education due to their potential to present learning materials in a visual and interactive manner. This study aims to evaluate the effectiveness of instructional videos in improving students’ critical thinking skills. The research employed a quasi-experimental method with a pretest–posttest control group design. The research subjects consisted of two classes: an experimental class that used instructional videos and a control class that employed conventional teaching methods. The research instrument was a critical thinking test measuring indicators such as analysis, evaluation, and inference. Data analysis was conducted using an independent samples t-test after meeting the assumptions of normality and homogeneity. The results showed that the average critical thinking score in the experimental class increased significantly compared to the control class, with an effect size indicating a moderate to high improvement. These findings confirm that instructional videos not only facilitate the understanding of abstract concepts but also stimulate students to think critically about the information presented. The value of this manuscript lies in its contribution to providing empirical evidence from the Indonesian educational context that the integration of video media can strengthen higher-order thinking processes among elementary school students. Practical implications include recommendations for teachers to select videos with relevant content, support post-viewing discussions, and provide opportunities for students to revisit the material so that critical thinking skills can develop optimally